2005
DOI: 10.1111/j.1365-2222.2005.02263.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels and gender difference of exhaled nitric oxide in Chinese schoolchildren

Abstract: This study demonstrates a gender difference of eNO level in healthy Chinese schoolchildren. When compared with Caucasians, Chinese children have significantly higher eNO levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
4
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 27 publications
8
49
4
1
Order By: Relevance
“…This result is in agreement with the works of Barreto et al 4 and Wong et al, 16 who recently demonstrated a sex difference in eNO levels in schoolchildren. Similarly, Nordvall et al, 17 in a large population sample, found a significantly higher eNO in boys than in girls.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with the works of Barreto et al 4 and Wong et al, 16 who recently demonstrated a sex difference in eNO levels in schoolchildren. Similarly, Nordvall et al, 17 in a large population sample, found a significantly higher eNO in boys than in girls.…”
Section: Discussionsupporting
confidence: 93%
“…Table 4 summarises the comparison of FeNO of normal adults without known lung diseases between different populations. Compared with the study performed in Sweden by OLIN et al [14] with 1131 subjects, [28]. Another large-scale paediatric study in Canada involving 656 school children aged 9-12 years also found that AsianCanadian subjects had a higher FeNO value than white subjects and the African-Canadian subjects [12].…”
Section: Discussionmentioning
confidence: 67%
“…Exhaled nitric oxide levels (a surrogate of eosinophilic inflammation) among obese asthmatic children may be the same or even reduced compared to similar leans. [134][135][136][137][138] A few studies in adult obese asthmatics have shown reduced eosinophilic inflammation compared with similar leans. 112,113 Obese asthmatic children did not have elevated airway LTB 4 .…”
Section: Airway Inflammationmentioning
confidence: 99%